Penggunaan Gadget Terhadap Perilaku dan Intensitas Komunikasi Keluarga (Studi Kasus Kecamatan Soreang Kota Parepare) - A. Nurul Mutmainnah; Nidaul Islam (KOMUNIDA : Media Komunikasi dan Dakwah, 2019)
he study of this article explains the communication behavior of family membersafter the onset of the gadget. In the current technological development, gadgets becometools that are not separated by humans in everyday life. Similarly, with family memberscan not be separated with gaget to support their daily activities. Communication is thekey to family harmony, but the presence of gadgets has an influence on familycommunication behavior. This article uses qualitative research methods by collectingobservation data, in-depth interviews, and other research supporting data. the results ofthis study found that the communication behavior of family members in using gadgets isdivided into two, namely proactive in communication, and reactive in familycommunication. Family communication in maintaining harmony is shown by the unctioning of parents in educating and always paying attention to their children, eitherby direct communication or through gadgets. Thus, the family remains harmoniousbecause family communication continues despite the presence of a gadget.